Writing instruction to support literacy success - Ortlieb, Evan.; Cheek, Earl H.; Verlaan, Wolfram (Bingley, U.K. : Emerald, 2016)
In recent years there has been a universal increase in expectations for academic writing alongside high-stakes tests, as students must master writing for pragmatic purposes including argumentative papers, dialogic narratives, and even research reports. All the while, research related to how to effectively prepare these students for success has been stymied with an over-emphasis on other areas of literacy. This volume features prominent international researchers who share their evidence-based successes partnering with teachers in K-12 classrooms, with particular emphasis on teaching writing products and processes in a digital age. As a result of its up-to-date focus on both print and digital literacies, the book will have wide readership amongst educators who work in the early childhood, elementary, middle, and high school years.
Rethinking writing products and processes in a digital age / Evan Ortlieb, Wolfram Verlaan, Earl H. Cheek Jr., Danielle DiMarco -- Turning around the progress of struggling writers: key findings from recent research / Sine<U+0301>ad Harmey, Emily Rodgers -- Accelerating student progress in writing: examining practices effective in New Zealand primary school classrooms / Judy M. Parr -- Ideas as a springboard for writing in K-8 classrooms / Kathleen Alley, Barbara J. Peterson -- Process with a purpose: low-stakes writing in the secondary English classroom / Sue Verlaan, Wolfram Verlaan -- Learning language and vocabulary in dialogue with the real audience: exploring young writers' authentic writing and language learning experiences / Ewa McGrail, J. Patrick McGrail, Alicja Rieger -- Understanding a digital writing cycle: barriers, bridges and outcomes in two second-grade classrooms / Jessica S. Mitchell, Rachael F. Thompson, Rebecca S. Anderson -- Classroom writing community as authentic audience: the development of ninth-graders' analytical writing and academic writing identities / Susan F. Fields -- Engaging students in multimodal arguments: infographics and public service announcements / Emily Howell -- The use of Google Docs technology to support peer revision / Jessica Semeraro, Noreen S. Moore -- A framework for literacy: a teacher-researcher partnership considers the'C-S-C paragraph' and literacy outcomes / Christopher W. Johnson -- Powerful writing instruction: seeing, understanding, and influencing patterns / Marla Robertson, Leslie Patterson, Carol Wickstrom -- Fourth graders as researchers: authors and self-illustrators of informational books / Anita Nigam, Carole Janisch -- Seniors, scholars, researchers: using an inquiry approach to writing the research paper / Sarah Fleming -- Augmenting academic writing achievement for all students / Wally Thompson, Debra Coffey.
Includes bibliographical references.
Print version record
Keywords: Education -- Teaching Methods & Materials -- General; Literacy strategies; Education -- Research; Report writing -- Study and teaching